Psychosocial and Developmental Characteristics of Female Adolescents Who Have Committed Sexual Offenses. (August 2014) - van der Put, Claudia; van Vugt, Eveline S.; Stams, Geert Jan J. M.; Hendriks, Jan
The present study aimed to examine differences in psychosocial and developmental characteristics between Adolescent Females who have committed Sexual Offenses (AFSOs; n = 40), Adolescent Females who have committed nonsexual Violent Offenses (AFVOs; n = 533), and Adolescent Males who have committed Sexual Offenses (AMSO, n = 743). Results showed that AFSOs and AMSOs were remarkably similar, whereas AFSOs and AFVOs were remarkably different on the measured variables. Compared to AFVOs, AFSOs less often had antisocial friends and problems in the domains of school (truancy, behavior problems, dropping out of school) and family (e.g., parental problems, poor authority and control, and run away from home). Victimization of sexual abuse outside the family and social isolation were found to be more common in AFSOs than in AFVOs. Victimization of sexual abuse outside the family was the only specific characteristic of female adolescent sexual offending, as this was more common in AFSOs than in both AMSOs and AFVOs.